DIGITAL INTELLIGENCE IN THE AGE OF ARTIFICIAL INTELLIGENCE - Mohammed Qelhas (Proceedings on Engineering Sciences, 2023)
This systematic review examines the current state of digital intelligence in the age of artificial intelligence. A total of 26 relevant papers were shortlisted for a review based on a keyword search of academic databases. The review looked at the literature relating to the fields of artificial intelligence, machine learning, deep learning, and other related fields to understand the current advances in digital intelligence. It considers the impact that digital intelligence has had on society in terms of economic, political, and social implications. The review also considers potential ethical concerns related to digital intelligence and its use in the age of artificial intelligence. Systems utilising artificial intelligence can benefit from considering its impact and digital intelligence and vice versa. This can lead to better quality systems.